Wave‐Driven Mean Flow Dynamics in Submerged Canopies. Issue 3 (4th March 2020) - van Rooijen, Arnold; Lowe, Ryan; Rijnsdorp, Dirk P.; Ghisalberti, Marco; Jacobsen, Niels G.; McCall, Robert
Abstract: The physical roughness (canopies) formed by organisms within aquatic ecosystems (e.g., seagrass, kelp, and mangroves) modifies the local wave‐driven hydrodynamics within coastal and estuarine regions. In wave‐dominated environments, an understanding of the mean wave‐driven flows generated within and above canopies is important, as it governs material transport (e.g., of nutrients, sediment, and biota). However, until recently the effect of submerged canopies on wave‐current interactions and the resulting mean (wave‐averaged) flow dynamics has received relatively little attention. In this study, a combination of wave flume experiments and numerical modeling is used to investigate the wave‐induced mean flow profiles in the presence of a submerged canopy. The measured velocities and vegetation forces were used to derive bulk drag and inertia coefficients, and to validate a nonhydrostatic 2DV wave‐flow model. The numerical model results were used to conduct an in‐depth analysis of the mean horizontal momentum terms responsible for driving the mean (horizontal) flow within and above the submerged canopies. We show that the mean canopy hydrodynamics are driven by vertical gradients in wave and turbulent Reynolds stresses, balanced by the mean canopy drag forces. The wave Reynolds stress gradient is the dominant force driving the in‐canopy mean flow and is directly related to the vorticity that is generated when the wave orbital motions become rotational near the canopy interface. This study provides new insight in the mechanisms responsible for wave‐driven mean flows within submerged canopies and guidance for how these hydrodynamics can be predicted in coastal wave‐circulation models. Plain Language Summary: Aquatic plants that grow in estuaries and coastal oceans (such as seagrass, kelp, and mangroves) have a considerable influence on water flow (currents) and on waves propagating toward the shore. However, mean flows generated by the waves interacting with aquatic vegetation (with time scales much longer than the individual wave periods) have not been comprehensively studied. This study provides a description of how submerged vegetation alters the mean wave‐driven flow structure. A combination of detailed experiments conducted in a wave flume and numerical simulations are used to show that the mean flow just above the vegetation is relatively strong (up to 20% to 50% of the maximum wave velocity above the canopy), while it is considerably weaker inside the vegetation. We identified three forces that govern the mean current profile: the wave Reynolds stress gradient, the turbulent Reynolds stress gradient, and the vegetation drag force. These forces are usually not accurately described in larger‐scale computer simulations of coastal processes. However, reliable simulation of processes in the coastal ocean such as sediment transport and nutrient exchange requires an accurate prediction of mean flows, and thus these forces need to be properly incorporated in computer models when applied to regions with aquatic vegetation. Key Points: Physical and numerical modeling is used to investigate the wave‐induced mean flow profiles in the presence of submerged vegetation The multilayered phase‐resolving wave‐ flow model was able to accurately reproduce the depth variation of the wave‐driven mean flow profiles Wave‐driven mean flows inside vegetation canopies are driven by vertical gradients in the wave and turbulent Reynolds stresses